Clinical outcomes in 1731 patients undergoing mitral valve surgery for rheumatic valve disease. Issue 10 (16th November 2017) - Kim, Wan Kee; Kim, Ho Jin; Kim, Joon Bum; Jung, Sung-Ho; Choo, Suk Jung; Chung, Cheol Hyun; Lee, Jae Won
Abstract : Objective: Unlike degenerative mitral valve (MV) disease, the advantages of valve repair procedure over replacement have been debated in rheumatic MV disease. This study aims to evaluate the impact of procedural types on long-term outcomes through analyses on a large data set from an endemic area of rheumatic disease. Methods: We evaluated 1731 consecutive patients (52.3±12.5 years; 1190 women) undergoing MV surgery for rheumatic MV disease between 1997 and 2015. Long-term survival and valve-related outcomes were compared between repair and replacement procedures. To adjust for selection bias, propensity score analyses were performed. Results: Patients undergoing repair were younger and had more predominant mitral regurgitation than mechanical and bioprosthetic replacement groups (61.6% vs 15.6% vs 24.4%; P<0.001). During follow-up (130.9±27.7 months), 283 patients (16.3%) died and 256 patients (14.8%) experienced valve-related complications. Propensity score matching yielded 188 pairs of repair and replacement patients that were well balanced for baseline covariates. In the matched cohort, there was no significant difference in the mortality risk between the repair and replacement groups (HR, 1.24; 95% CI 0.62 to 2.48). The risk of composite valve-related complications, however, was significantly lower in repair group (HR, 0.57; 95% CI 0.33 to 0.99) principally derived by a lower risk of haemorrhagic events (HR, 0.23; 95% CI 0.07 to 0.70). The incidence of reoperation was not significantly different between groups in the matched cohort (HR, 1.62; 95% CI 0.49 to 5.28). Conclusion: Valve repair in well-selected patients with severe rheumatic MV disease led to comparable survival, but superior valve-related outcomes compared with valve replacement surgery.